Reconsidering the 1095 novella of Alexios I Komenenos: A testimony to the Byzantinization of the Slavic population - Ilić Tamara (Zbornik Radova Vizantološkog Instituta)
The Novella issued by the Byzantine emperor Alexios I Komnenos in 1095 regulates the process of proving freedom for persons descended from “Bulgarians and the like” and the introduction of mandatory religious marriage, which scholarship tends to interpret as the full penetration of the Christian notion of grace into these spheres of life. The text of this Novella, abridged, slightly revised, and in Old Serbian translation, reappears in the Nomokanon of St. Sava and some subsequent Old Russian Nomokanons. This paper employs the historical method and linguistic analysis of a range of sources to explore the role of this law in the process of the Byzantinization of the Slavic population.